الألفاظُ المُعَرَّبة في فتح الباري بشرح صحيح البخاري لإبن حجر العسقلاني - أ.د. حسین محیسن ختلان البكري (College of Education for Women, 2019)
This research deals with a range of vocabulary, non-Arab, which appeared in a book Fath al-Baari by Ibn Hajar al-Askalani, so we display this vocabulary and matrix is scholarly tuned in, interpretation and statement of origin, and then matrix is what I'm stone in the view of the scientists and was for Ibn Hajar outstanding efforts in the follow-up statements The scientists documented a valuable book and it is fath Al-Bari important source of vocabulary Aloagamip the complexity and multiplicity of views.